2003
DOI: 10.1051/0004-6361:20021721
|View full text |Cite
|
Sign up to set email alerts
|

A deep VLA survey at 6 cm in the Lockman Hole

Abstract: Abstract.We have obtained a deep radio image with the Very Large Array at 6 cm in the Lockman Hole. The noise level in the central part of the field is ∼11 µJy. From these data we have extracted a catalogue of 63 radio sources with a maximum distance of 10 arcmin from the field center and with peak flux density greater than 4.5 times the local rms noise. The di fferential source counts are in good agreement with those obtained by other surveys. The analysis of the radio spectral index suggests a flattening of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
182
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(196 citation statements)
references
References 53 publications
11
182
3
Order By: Relevance
“…The circles of Bolocam, SCUBA, and MAMBO observations correspond to 2 confidence regions of position, including both beam sizes and stated pointing errors. The 6 cm VLA radio sources of Ciliegi et al (2003) and unpublished 21 cm VLA sources of M. Yun (2004, private communication), with average noise levels of 11 and 10-15 Jy beam À1 , respectively, are identified. The M. Yun (2004, private communication) radio field covers the entire Bolocam good coverage region, while the center of Ciliegi et al (2003) observations is offset to the northwest, with an overlap of approximately 130 arcmin 2 .…”
Section: Comparison With Other Submillimeter and Millimeter-wave Surveysmentioning
confidence: 97%
See 1 more Smart Citation
“…The circles of Bolocam, SCUBA, and MAMBO observations correspond to 2 confidence regions of position, including both beam sizes and stated pointing errors. The 6 cm VLA radio sources of Ciliegi et al (2003) and unpublished 21 cm VLA sources of M. Yun (2004, private communication), with average noise levels of 11 and 10-15 Jy beam À1 , respectively, are identified. The M. Yun (2004, private communication) radio field covers the entire Bolocam good coverage region, while the center of Ciliegi et al (2003) observations is offset to the northwest, with an overlap of approximately 130 arcmin 2 .…”
Section: Comparison With Other Submillimeter and Millimeter-wave Surveysmentioning
confidence: 97%
“…The 6 cm VLA radio sources of Ciliegi et al (2003) and unpublished 21 cm VLA sources of M. Yun (2004, private communication), with average noise levels of 11 and 10-15 Jy beam À1 , respectively, are identified. The M. Yun (2004, private communication) radio field covers the entire Bolocam good coverage region, while the center of Ciliegi et al (2003) observations is offset to the northwest, with an overlap of approximately 130 arcmin 2 . Also shown are the 20 published radio sources from deep 21 cm VLA observations (average noise level of 4.8 Jy beam À1 ) from Ivison et al (2002) that are coincident with SCUBA sources, as well as an additional 21 cm VLA source discovered by Egami et al (2004) from the reexamination of the Ivison et al (2002) map.…”
Section: Comparison With Other Submillimeter and Millimeter-wave Surveysmentioning
confidence: 97%
“…The radial probability distribution of the separation between submm source and the shorter wavelength galaxies is denoted by f (r). This likelihood ratio (LR) method was developed in Sutherland & Saunders (1992) with additional improvements in Ciliegi et al (2003), Brusa et al (2007) and−in the context of submillimeter data−in Chapin et al (2011). This likelihood ratio estimator is similar to the calculation of "p-values," or the corrected-Poissonian probability.…”
Section: Radio Counterpartsmentioning
confidence: 99%
“…The radio catalogue includes 883 sources. Using a likelihood ratio technique (Ciliegi et al 2003), the optical/infrared counterparts of the radio sources have been identified (Bonzini et al 2012). Excluding the outermost region as defined in Bonzini et al (2012), the wealth of multi-wavelength data available for the E-CDFS allows robust estimates of photometric redshifts (Santini et al 2009;Taylor et al 2009;Cardamone et al 2010;Rafferty et al 2011).…”
Section: Radio Datamentioning
confidence: 99%